Recombinant Influenza Vaccines: Saviors to Overcome Immunodominance - Mathew, Nimitha R.; Angeletti, Davide (Frontiers in Immunology, 2020)
It has been almost a decade since the 2009 influenza A virus pandemic hit the globe causing significant morbidity and mortality. Nonetheless, the annual influenza vaccination, which elicits antibodies mainly against the head region of influenza hemagglutinin (HA), remains as the mainstay to combat and reduce symptoms of influenza infection. Influenza HA is highly antigenically variable, thus limiting vaccine efficacy. Additionally, the HA head occupies the upper strata of the immunodominance hierarchy thereby clouding the antibody response towards subdominant epitopes, which are usually conserved across different influenza strains. Isolation of monoclonal antibodies from individuals recognizing such epitopes has facilitated the development of recombinant vaccines that focus the adaptive immune response towards conserved, protective targets. Here we review some significant leaps in recombinant vaccine development, which could possibly help to overcome B cell and antibody immunodominance and provide heterosubtypic immunity to influenza A virus.